The Age of Exploited Persons in Romania – Is There A Difference by Sex, Type of Residency, Type of Exploitation, Relationship with The Recruiter or Country of Destination? - Glăvan Ionela-Roxana; Mirică Andreea; Necula Marian (Communications of International Proceedings, 2020)
This study focuses on the findings revealed for the age of exploited persons in Romania, specifically through analysing differences by demographic characteristics in relation to the human trafficking phenomenon. The dataset that is modelled and analysed in this study originates from the National Agency against Trafficking in Persons in Romania (ANTIP). Analysis on the selected dataset points out that non-parametric procedures are more suitable. Due to heterogeneity of the age the median is more relevant than the mean thus the results of the Independent-Samples Median Test for variable “Age” across categories show a significant difference across categories for most of the variables, except for Type of residency.  Boxplots where significant differences occurred are further presented for the variable “Age” across categories of the variables in order to describe the present variable distributions.
Keywords: exploitation; vulnerability; age; human trafficking; Romania